(3cJGH haGI Cgd GdHjJ hCjf OafhGs - (3CHh eMeO, GHf GdNTGH, YHO Gddg Hf CMeO, J(B567(3g`s ((3Ydjs)
(3ChdgG (B:s
...(3CNHQfG GdSjO(B...(3Uaj GdOjf CHh LYaQeMeO(B...(3GdehShj aj GdYTQ GdCNjQ ef UaQ ef SfI SJI YTQI hSJeGFI(B...s
(3BNQgG (B:s
...(3MOKfj eMeO Hf ehSi GdWhSj(B...(3bGd jbGd cfjI GdNda GdUGdM CHh GdbGSe hgh Ph GdGSejf(B...s
(3fSNI ebGHdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B4(3,U(B67s
(3GdPQjYI(B:(3L(B3(3,U(B120(3,Qbe(B805s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJGQjNs